PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN PENGUASAAN KONSEP ELASTISITAS PADA SISWA SMA - Prima, Eka Cahya; Kaniawati, Ida (Jurnal Pengajaran MIPA, 2011)
Low mastery of physics concepts due to lack of process skills which it was trained in the learning process. The observation result that the failure to achieve mastery of concepts in physics due to some subject-oriented learning process in practice only a matter of course in learning cognitive aspects. Learning model problem based learning with inquiry approach is able to train and involve students' process skills to solve a problem through the stages of the scientific method. This study aims to measure the increase in the mastery of concepts and science process skills after application of the learning model are compared with the conventional model. The design used in this study is to pretest and posttest control group study with a sample of students grade XI IPA-6 and XI IPA-7 in high school one of Bandung, which is determined by purposeful sampling technique. The results showed that the significant influence the implementation of the learning model to increase mastery of the concept of elasticity in the experimental class with high category (g = 0.77) higher increase than the control class who were categorized (g = 0.50), the existence of significant influence implementation of the learning model of science process skills enhancement with high category (g = 0.87) higher increase than the control class increased with category (g = 0.59). And the linear correlation (Ftc=3,2F(0,99.(5â„33)=3,635) positive improvement of science process skills to increase after application of the concept of mastery learning model is categorized high (0.508Ï0.887).